2002
DOI: 10.1021/jf020657z
|View full text |Cite
|
Sign up to set email alerts
|

Application of the 2,2‘-Azinobis(3-ethylbenzothiazoline-6-sulfonic acid) Radical Cation Assay to a Flow Injection System for the Evaluation of Antioxidant Activity of Some Pure Compounds and Beverages

Abstract: The 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS •+ ) assay was adapted to a flow injection (FI) system to obtain a sensitive and rapid technique for the monitoring of antioxidant activity of pure compounds and complex matrixes, such as beverages and food extracts. The FI system includes a HPLC pump that flows the mobile phase (a solution of ABTS •+ in ethanol) through a 20 µL loop injector, a single bead string reactor filled with acid-washed silanized beads, a delay coil and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 24 publications
7
95
0
2
Order By: Relevance
“…The setting potential was 0, 100, 200, 300 and 400 mV (v. Palladium reference electrode) and the chromatographic separation was obtained applying an isocratic elution at flow rate of 0.8 ml/min. Total Antioxidant Capacity, carotenoids, polyphenols and total vitamin C were measured as follow: total antioxidant capacity (TAC) using two different assays Ferric Reducing Antioxidant Power (FRAP) (Benzie & Strain, 1996) and Trolox Equivalent Antioxidant Capacity (TEAC) method (Pellegrini et al, 2003;Re et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The setting potential was 0, 100, 200, 300 and 400 mV (v. Palladium reference electrode) and the chromatographic separation was obtained applying an isocratic elution at flow rate of 0.8 ml/min. Total Antioxidant Capacity, carotenoids, polyphenols and total vitamin C were measured as follow: total antioxidant capacity (TAC) using two different assays Ferric Reducing Antioxidant Power (FRAP) (Benzie & Strain, 1996) and Trolox Equivalent Antioxidant Capacity (TEAC) method (Pellegrini et al, 2003;Re et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, methanol extracts (5 g of raw vegetables in 80 mL of a 70% methanol solution) were obtained from a mean representative sample by shaking the fresh plant material in an Elpan, 357 water bath shaker at ambient temperature for 2 h. They were then centrifuged using a MPW-340 centrifuge, fi ltered and fi nally stored at -22°C [Pellegrini et al, 2003].…”
Section: Preparation Of Methanol Extractsmentioning
confidence: 99%
“…Data on TAC were included in the data bank on a number of foods directly analyzed in our laboratory and representative of the average Northern Italian diet (Pellegrini et al, 2003a;Pellegrini et al, 2006). Dietary TAC values used in this study have been obtained by applying the Trolox equivalents antioxidant capacity assay (Pellegrini et al, 2003b), expressed as TAC in mmol of Trolox/kg of fresh food, and reported as mmol of Trolox/day.…”
Section: Dietary Datamentioning
confidence: 99%